SOSIAL EKONOMI MASYARAKAT SEKITAR TPI DI NAGARI KAMBANG BARAT KECAMATAN LENGAYANG KABUPATERN PESISIR SELATAN - syefriani, Desi; Dasrizal, Dasrizal; Farida, Farida (STKIP PGRI Sumbar, 2014)
ABSTRACT This study aimed to describe the Community Social economics around TPI at Village Kambang Lengayang pesisir selatan District.This type of research is classified as descriptive research. This study population is the entire population of 6627 inhabitants with 1298 household. Samples were taken in two ways, the sample region taken with proportional random sampling technique, which is 2 villages in the West Kambang Villages with the proportion of 25% of the total sample size as 84 families (KK). Collecting data using guided inquiry, statistical analysis used is descriptive by using a percentage formula. The results showed as follows : ( 1 ). The level of income communities around the TPI at Kambang in one month in general Rp 1.500.000. Family members rarely have aside job income on the job side in one month is Rp 500.000, and general living needs are met. ( 2 ) The level of public education general is the primary level. Location of school in the vellage in and the source of childrens education in general own expense. ( 3 ). Public health conditions around TPI Village Kambang. judging from the type of disease that often affects the family in general fever. The treatment suffered frequented is the distance of the health center and home treatment of about 5 km, and the source of costs for private medical treatment in general. ( 4 ). Social relations around TPI Villages Kambang viewed from either the nuclear family, relationships with relatives quite good, quite good relations with neighbors, and in the everyday environment is quite good, a strong culture of family life .